2010
DOI: 10.1159/000319648
|View full text |Cite
|
Sign up to set email alerts
|

Increased ACE and Decreased ACE2 Expression in Kidneys from Patients with IgA Nephropathy

Abstract: Background: Angiotensin-converting enzyme (ACE)2 forms angiotensin-1–7 which may protect kidney in a counterregulatory manner to angiotensin II. Recent studies revealed increased ACE and decreased ACE2 expression in kidneys of patients with diabetic nephropathy. However, these changes may not be specific for diabetic nephropathy. We studied ACE and ACE2 expression in patients with IgA nephropathy. Methods: Renal ACE and ACE2 expression was assessed by immunohistochemistry and in situ hybridization in 30 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 57 publications
(32 reference statements)
3
31
0
1
Order By: Relevance
“…This is consistent with the findings in animal models of hypertension [32], although renal ACE2 expression and activity is unaltered during established hypertension in adult SHR-SP and TGR(mREN2)27 rats [33]. Furthermore, it is reported that ACE2 staining is decreased and ACE staining is increased in glomeruli in adult IgAN patients [34]. These results are different from the findings of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the findings in animal models of hypertension [32], although renal ACE2 expression and activity is unaltered during established hypertension in adult SHR-SP and TGR(mREN2)27 rats [33]. Furthermore, it is reported that ACE2 staining is decreased and ACE staining is increased in glomeruli in adult IgAN patients [34]. These results are different from the findings of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Sensitive indicators of ROS production, lipid peroxidation products and the glomerulosclerosis score were markedly enhanced in those mice while ARB prevented these increases, which strongly supports the notion that ACE2 plays a role in Ang II-induced glomerular injury. More recently, a similar relationship between ACE2 and ACE expression in diseased glomeruli was reported even in patients with IgAN [43]. …”
Section: Involvement Of the Glomerular Ras In Disease Progressionsupporting
confidence: 66%
“…Increased salt intake and related kidney damage were associated with reduced cortical expression of ACE2 in obese Zucker rats (69) and increased ACE/ACE2 mRNA and protein ratio in glomeruli of uninephrectomized WKY (70), respectively. The similar ratio between ACE and ACE2 was also found in renal biopsies from patients with hypertension when compared to subjects with normal blood pressure (71) as well as in patients with IgA nephropathy (72) and diabetes (57;73). No differences in ACE2 expression between patients with focal segmental glomerulosclerosis and control cohort has been reported (73); these data suggested that decrease in ACE2 is not a general response to kidney injury.…”
Section: Renoprotective Role Of Ace2supporting
confidence: 64%